2018
DOI: 10.1103/physrevlett.120.037602
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall Orientations in Ferroelectric Superlattices Probed with Synchrotron X-Ray Diffraction

Abstract: Ferroelectric domains in PbTiO_{3}/SrTiO_{3} superlattices are studied using synchrotron x-ray diffraction. Macroscopic measurements reveal a change in the preferential domain wall orientation from {100} to {110} crystallographic planes with increasing temperature. The temperature range of this reorientation depends on the ferroelectric layer thickness and domain period. Using a nanofocused beam, local changes in the domain wall orientation within the buried ferroelectric layers are imaged, both in structurall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…In these artificially layered materials, ordered nanoscale domains form within the ultrathin ferroelectric layers to minimize the depolarization field energy associated with the unscreened polarization [1][2][3]. Motivated by theoretical predictions of complex polarization structures, unusual switching behavior, and high-frequency dynamics [4][5][6][7][8][9], the properties of nanodomains in ferroelectric superlattices have been widely investigated using laboratory and synchrotron x-ray diffraction as a function of applied field, temperature, and optical excitation [3,[10][11][12][13][14][15][16][17][18][19][20][21]. Direct imaging of the domains using scanning probe techniques is challenging due to their small sizes and buried nature, and it has been mainly restricted to ferroelectric-dielectric bilayers and trilayers, or superlattices with larger domains [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In these artificially layered materials, ordered nanoscale domains form within the ultrathin ferroelectric layers to minimize the depolarization field energy associated with the unscreened polarization [1][2][3]. Motivated by theoretical predictions of complex polarization structures, unusual switching behavior, and high-frequency dynamics [4][5][6][7][8][9], the properties of nanodomains in ferroelectric superlattices have been widely investigated using laboratory and synchrotron x-ray diffraction as a function of applied field, temperature, and optical excitation [3,[10][11][12][13][14][15][16][17][18][19][20][21]. Direct imaging of the domains using scanning probe techniques is challenging due to their small sizes and buried nature, and it has been mainly restricted to ferroelectric-dielectric bilayers and trilayers, or superlattices with larger domains [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The lattice parameters of a material under an electric field can be measured in bulk and thin-film specimens with sufficiently large volume by using in situ X-ray diffraction [7][8][9][10] . Furthermore, nanoprobe X-ray diffraction has advanced rapidly in recent years [11][12] and has been used to investigate the local structures of ferroelectric materials [13][14] . This capability should help in studying nanoscale polar structures such as "polar nanoregions" [15,16] and lamellar-like nanodomains [17][18][19][20] , as well as defect structures such as surface, interface, and grain boundaries, along with nanoscale objects such as nanoparticles [21,22] .…”
mentioning
confidence: 99%
“…Hadjimichael et al [119] recently demonstrated the potential of diffuse scattering for nanoscale investigation of domain and domain wall architecture in ferroelectric PTO/STO superlattices. Local reciprocal space maps (RSM) were measured around the out-of-plane (002) Bragg PTO reflection.…”
Section: Accessing the Domain State In Ferroic Multilayersmentioning
confidence: 99%
“…Spatially scanning the area at the x-ray angles of the satellite peaks in the (100), (110) and (010) direction around the defect shows the domain type dependence on the defect shape, i.e., the domains lie parallel to the lines of the defect. Reprinted with permission from [119]. ( b ) SHG images of voltage-poled 180° domain walls in PZT films grown on SRO buffered (DSO) show the total in-plane polarization, the polarization parallel to the ( c ) [001] DSO direction and ( d ) [110] DSO direction.…”
Section: Figurementioning
confidence: 99%